Incorporating EFL websites in class: Bangladeshi teachers’ perceptions (Journal of NELTA, 2018)
Incorporating Information-Technology in classes is revolutionizing English language teaching (ELT) practices. Since teachers are the key personnel, their attitudes towards the process determine its success. This study presents the results of a study investigating Bangladeshi university level English as a foreign language (EFL) teachers’ perceptions of incorporating EFL websites in their classes. The findings revealed that private university teachers’ have more positive attitude than public university teachers do. In addition, both private and public university teachers reported of logistic limitations and systematic complications in their respective institutions. Following this, the study proposes enhancing administrative collaborations, arranging teacher-student skill development programmes, and creating customized websites for Bangladeshi ELT contexts.